Wage Indexation and Compensating Wage Differentials - Hendricks, Wallace E.; Kahn, Lawrence M. (The Review of Economics and Statistics, 1986)
A stractThe theory of wage indexation implies that if workers are more risk averse than firms, then workers will pay a price in order to obtain wage indexation. This prediction is tested on a sample of 3,115 U.S. manufacturing collective bargaining negotiations from 1967 to 1982. The dependent variable is the expected real wage level taking into account expected cost of living payments (Colas). Using instrumental variables or fixed effects techniques to account for the endogeneity of indexation, ve find a 2% to 22% real wage premium paid to get a Cola. However, the 2% figure is most consistent with existing estimates of worker risk aversion and union-nonunion wage differentials.